A Review of Cryptocurrency in the Digital Economy - Sitthipon, Tamonwan; Kaewpuang, Pichart; Auttawechasakoon, Pichakoon (International Journal of Computing Sciences Research, 2023)
Purpose – Cryptocurrency in the digital economy plays a vital role and is growing exponentially. This article aims to review cryptocurrency in the digital economy. Method – A narrative synthesis was employed. Moreover, the researchers conducted a systematic documentary review and used content analysis to analyse the data. The literature was reviewed systematically to describe cryptocurrency in the digital economy. The literature and information were obtained from various books and research articles on EBSCO, Google Scholar, Scopus, Web of Science, and ScienceDirect. The inclusion criteria were studies that clearly defined the cryptocurrency in the digital economy, were published and written in English and were peer-reviewed. Results – The results reveal that cryptocurrency is a subset of digital currency that has increased. Furthermore, the opportunities and challenges of cryptocurrency are critical to the economic systems of many countries in the digital economy. Conclusion – Cryptocurrency in the digital economy is essential. Thus, it is crucial to pay close attention to cryptocurrency to improve and grow economic systems. Recommendations – The recommendation is to consider empirical research. Moreover, it is recommended to consider a quantitative study, such as online surveys. A qualitative approach, such as online interviews, could also give insight results and a clear view. Research Implications – This review article contributed to the existing literature on cryptocurrency in the digital economy. Hence, it could guide future research on cryptocurrency in the digital economy. Moreover, the implications could be applied to any sector to better understand and implement appropriate strategies regarding cryptocurrency in the digital economy.